Affective Art (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue on “Affective Art” includes papers that span the history of Western art from the Byzantine period to the present, addressing the emotions that works of art and architecture can arouse, ranging from fear, shame, sexual arousal, delight, elation, disgust, empathy, and more. Literary scholars have examined sentiment, and, recently, several art historians have begun to explore those eighteenth- and nineteenth-century images intended to evoke an empathetic feeling in the viewer, akin to the period concept of “sensibility”. Few artworks do not evoke at least a token emotion, but these can move us with their beauty—a sheer aesthetic response. This Special Issue, therefore, explores how art evokes its response. There are three large categories into which we can divide affective imagery: religious and devotional; sexual; and political. The largest category of works addressed here is religious. In his pioneering study of such pictures, The Power of Images (1989), David Freedberg considered the history of iconoclasm and censorship—the preventive measures that have attempted, across the centuries, to suppress affective responses to artworks. Also studied here are the unnamable emotions generated by modern abstract art and recent responses to political events, such as the removal of Confederate statues.